PENGARUH DESENTRALISASI FISKAL TERHADAP PERTUMBUHAN EKONOMI DAN TINGKAT KEMISKINAN DI PROVINSI SUMATERA BARAT - Marya, Meri; Handra, Hefrizal (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This research aims to analyze the impact of fiscal decentralization on economic growth and poverty levels in West Sumatra Province. Fiscal decentralization is a concept where the authority and responsibility in public financial management are transferred from the central government to local governments. West Sumatra Province was chosen as the study location because it is one of the provinces that significantly implements fiscal decentralization. This research method utilizes secondary data collected from the Central Statistics Agency (BPS) and related documents. Data analysis is conducted using panel regression methods over specific time periods. The research findings indicate that fiscal decentralization has a significant influence on economic growth in West Sumatra Province. Additionally, it was found that the poverty level is also influenced by fiscal decentralization, although its impact is not as pronounced as its influence on economic growth. These findings have important implications for government policies related to public financial management and poverty alleviation at the regional level. With a better understanding of the relationship between fiscal decentralization, economic growth, and poverty levels, it is hoped that more effective policies can be designed to improve the welfare of the population in West Sumatra Province and other regions.